Explaining the Geographic Pattern of Plant Invasion in 67 Nature Reserves in China - Chen, Shengbin; Chen, Zhiyang; Huang, Wenjie; Shao, Changliang; Mao, Lingfeng; Slik, Johan Willem Frederik (Frontiers in Ecology and Evolution, 2021)
Biological invasion is a serious threat to biodiversity and ecosystem function in nature reserves. However, the knowledge on the spatial patterns and underlying mechanisms of plant invasions in nature reserves is still limited. Based on a recent dataset on both invasive and native plants in nature reserves of China, we used regression and variation partitioning methods to statistically assess the relative roles of the “human activity”, “biotic acceptance” and “environmental heterogeneity” hypotheses in explaining the spatial variance of plant invasion levels. A total of 235 invasive plant species were compiled from 67 nature reserves. The high explanatory power of the human activity variables supported the “human activity” hypothesis. The “biotic acceptance” hypothesis was weakly supported, since no significant correlations between climatic variables and invasion level were found, when the effects of the other factors were controlled. The “environmental heterogeneity” hypothesis was mixed supported, since the number of native plants, representing environmental heterogeneity at fine scale explained considerable proportion of spatial variance of invasive plants but not that of proportion of invasive plants. We predict that nature reserves with high plant diversity affected by rapid economic development and increasing temperature will face a serious threat of exotic plant invasion. In conclusion, our results provide crucial information for spatial risk assessment and effective management of invasive plants in nature reserves.